2018
DOI: 10.1159/000490949
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Post-Progression Survival on Overall Survival in Elderly Patients with Non-Small-Cell Lung Cancer Harboring Sensitive EGFR Mutations Treated with First-Line EGFR Tyrosine Kinase Inhibitors

Abstract: Background/Aims: More than 50% of patients with lung cancer are aged > 65 years, and non-small-cell lung cancer (NSCLC) accounts for 85% of all cases of lung cancer among both elderly and adult patients. Subsequent therapies confound the capability to discern the effect of first-line chemotherapy on overall survival (OS). Therefore, using individual-level data, our study aimed to determine the relationships of progression-free survival (PFS) and post-progression survival (PPS) with OS after first-line epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…11 Several studies found that PPS following first-line chemotherapy for advanced NSCLC at the clinical trial level is strongly correlated with OS; 14,15 similar studies examined the impact of PPS in ED-SCLC and advanced NSCLC based on individual patient-level analysis of the strong correlation between OS and PPS. [16][17][18][19]28,29 In contrast to the previous reports, 26,27 we found that PFS does not necessarily reflect OS in patients with ED-SCLC treated with AteCE, but rather that PPS strongly influences OS. The results show that PFS is shorter than PPS, PPS influences OS intimately, and the relationship is linear.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…11 Several studies found that PPS following first-line chemotherapy for advanced NSCLC at the clinical trial level is strongly correlated with OS; 14,15 similar studies examined the impact of PPS in ED-SCLC and advanced NSCLC based on individual patient-level analysis of the strong correlation between OS and PPS. [16][17][18][19]28,29 In contrast to the previous reports, 26,27 we found that PFS does not necessarily reflect OS in patients with ED-SCLC treated with AteCE, but rather that PPS strongly influences OS. The results show that PFS is shorter than PPS, PPS influences OS intimately, and the relationship is linear.…”
Section: Discussioncontrasting
confidence: 99%
“… 11 Several studies found that PPS following first‐line chemotherapy for advanced NSCLC at the clinical trial level is strongly correlated with OS 14 , 15 similar studies examined the impact of PPS in ED‐SCLC and advanced NSCLC based on individual patient‐level analysis of the strong correlation between OS and PPS. 16 , 17 , 18 , 19 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations